SOFTWARE FOR IMAGE PROCESSING OF IRON-CARBONACEOUS ALLOY MICROSTRUCTURES - A. N. Chichko; S. G. Likhouzov; O. A. Sachek; W. F. Sobolev; O. I. Chichko (Наука и техника)
The paper proposes a mathematical apparatus for image processing of a cast-iron microstructure of a pearlite class that has casually distributed graphite inclusions in the structure the software has been developed and it allows to determine statistical functions concerning distribution of graphite inclusion characteristics according to areas, perimeters and distances between inclusions. The paper shows that computer processing of gray pig-iron microstructure image makes it possible to classify microstructures on the basis of statistical distribution of a graphite phase which are considered as indiscernible while applying conventional metallographic methods and it has practical significance for investigation of the interrelations – «workability – cast iron microstructure».